Marketing 2018
DOI: 10.5772/intechopen.74326
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacy Marketing in the New Era: A Global Picture of Extended Community Pharmacy Services

Abstract: The community pharmacists (CPs) are legally responsible to hand out a wide range of ready-made prescription medications to patients. Additionally, CPs are also involving in advocating customers who determine to self-medicate. Interestingly, it is also noted that CPs in developed countries like the United Kingdom, Germany, and Canada have performed more than these services. What are the extended community pharmacy services available? What are the barriers and perceptions of these extended services? It is ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The study suggests that community pharmacists should provide person-centric care, including lifestyle recommendations like smoking cessation, weight management and exercise advice for conditions like cardiovascular diseases and asthma (Hassali et al, 2018 ; Rosenthal et al, 2018 ). However, it has also been reported that patients often perceive pharmacists as ‘medical professionals’ rather than wellness experts, which may affect their willingness to engage in discussions about healthy lifestyle choices (Blebil et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study suggests that community pharmacists should provide person-centric care, including lifestyle recommendations like smoking cessation, weight management and exercise advice for conditions like cardiovascular diseases and asthma (Hassali et al, 2018 ; Rosenthal et al, 2018 ). However, it has also been reported that patients often perceive pharmacists as ‘medical professionals’ rather than wellness experts, which may affect their willingness to engage in discussions about healthy lifestyle choices (Blebil et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, they shall irresponsibly withdraw themselves from the situation to search for another act of assistance, which is able to carry out the role as expected. Therefore, it is critical to ensure that the CPs indulge themselves with the facts, information, and skills acquired through experience or education as the way to cause the people to believe firmly in the truth of the CPs' competence to counsel them [37]. The CPs should also make alterations to their way in which one acts or conducts oneself, especially toward the interaction with their customers.…”
Section: Categories Of Drug-related Problemsmentioning
confidence: 99%
“…Therefore, many companies are willing to spend millions of dollars to ensure their products shall reflect acquiescence perception to the customers' senses. In the healthcare context, the CPs must always make better of their services to catch the attention among the people to notice them or their services as interesting or important [37]. The CPs must intensify, increase, or further improve the quality, value, or extent of their knowledge and skills so that they shall have the chance to demonstrate the truth or existence of something by evidence or argument.…”
Section: Categories Of Drug-related Problemsmentioning
confidence: 99%
“…A medicine use review involves a private discussion between a pharmacist and a patient, in order to improve the medication adherence and to lower the risk of adverse drug reaction due to polypharmacy [8]. Pharmacists can identify which medicines a patient may not be taking, as well as potentially inappropriate medicines [2; 7].…”
Section: Pharmaceutical Care and Medicine Use Reviewmentioning
confidence: 99%